Asset Pricing with Concentrated Ownership of Capital - Kevin J. Lansing (Norges Bank, 2011)
This paper investigates how concentrated ownership of capital influences the pricing of risky assets in a production economy. The model is designed to approximate the skewed distribution of wealth and income in U.S. data. I show that concentrated ownership significantly magnifies the equity risk premium relative to an otherwise similar representative-agent economy because the capital owners' consumption is more strongly linked to volatile dividends from equity. A temporary shock to the technology for producing new capital (an "investment shock") causes dividend growth to be much more volatile than aggregate consumption growth, as in long-run U.S. data. The investment shock can also be interpreted as a depreciation shock, or more generally, a financial friction that affects the supply of new capital. Under power utility with a risk aversion coeffecient of 3.5, the model can roughly match the first and second moments of key asset pricing variables in long-run U.S. data, including the historical equity risk premium. About one-half of the model equity premium is attributable to the investment shock while the other half is attributable to a standard productivity shock. On the macro side, the model performs reasonably well in matching the business cycle moments of aggregate variables, including the pro-cyclical movement of capital's share of total income in U.S. data.
hdl:11250/2496941
Keywords: E25; E32; E44; G12; O40; 330; asset pricing; equity premium; term premium; investment shocks; real business cycles; wealth inequality